PENGARUH CATCALLING TERHADAP KEPERCAYAAN DIRI MAHASISWA PROGRAM STUDI BKI FAKULTAS DAKWAH UIN SMH BANTEN: FAKULTAS DAKWAH UIN SMH BANTEN - Siti Alifah; Hunainah (QATHRUNÂ, 2025)
This research aims to: 1) examine the depiction of catcalling among students, 2) examine the depiction of self-confidence among students, 3) determine whether catcalling affects the self-confidence of students. This study uses a descriptive quantitative approach. The population in this study is active students of the Islamic Counseling Guidance Study Program from the 2022 cohort at the Faculty of Dawah, UIN SMH Banten, totaling 156 students. The sample in this study consists of students from the Islamic Counseling Guidance Study Program from the 2022 cohort at the Faculty of Dawah, UIN SMH Banten, with 61 respondents, selected using purposive sampling technique. The instruments used in this study are questionnaires on catcalling and self-confidence. The measurement tool used in this study is the Likert scale. Data analysis techniques employed descriptive analysis and inductive analysis which include normality tests, homogeneity tests, and hypothesis tests. The hypothesis testing was conducted using simple linear regression analysis with the assistance of IBM SPSS version 30 for Windows. The results of the study found that: 1) catcalling among students of the BKI Program from the 2022 cohort at the Faculty of Dawah, UIN SMH Banten is at an interval of 43-52, categorized as high, with a percentage of 48%. 2) self-confidence among students of the BKI Program from the 2022 cohort at the Faculty of Dawah, UIN SMH Banten is at an interval of 17-29, categorized as very low, with a percentage of 69%. 3) based on the results of the simple linear regression analysis regarding catcalling and self-confidence, a t-value of -4.224 > t-table of 2.001 was obtained. This indicates that there is a significant negative effect of catcalling on the self-confidence of students of the BKI Program from the 2022 cohort at the Faculty of Dawah, UIN SMH Banten, thus Ha is accepted and H0 is rejected.